Sex‐specific associations between traumatic experiences and resting‐state functional connectivity in the Philadelphia Neurodevelopmental Cohort - Shiying Wang; Jeffrey G. Malins; Heping Zhang; Jeffrey R. Gruen (Wiley, 2021)
Abstract Background Traumatic experiences during childhood or adolescence are a significant risk factor for multiple psychiatric disorders and adversely affect multiple cognitive functions. Resting‐state functional magnetic resonance imaging has been used to investigate the effects of traumatic experiences on functional connectivity, but the impact of sex differences has not been well documented. This study investigated sex‐specific associations between resting‐state functional connectivity (rsFC) and traumatic experiences in typically developing youth. Methods The sample comprised 1395 participants, aged 8-21 years, from the Philadelphia Neurodevelopmental Cohort. Traumatic experiences were assessed based on the structured psychiatric evaluation. Sex, the number of traumatic events, and their interaction were regressed onto voxel‐wise intrinsic connectivity distribution parameter values derived from resting‐state functional magnetic resonance imaging. Brain regions that passed cluster correction were used as seeds to define resting‐state networks. Results After quality control, the final sample had 914 participants with mean (SD) age 14.6 (3.3) years; 529 (57.8%) females; 437 (47.8%) experienced at least one kind of traumatic event. Four discrete anatomical clusters showed decreased functional connectivity as the number of traumatic events increased. The resting‐state networks defined by using these four clusters as seeds corresponded with the somatomotor network. Sex‐specific associations were identified in another three clusters for which males showed increased connectivity, and females showed decreased connectivity as the number of traumatic events increased. The resting‐state networks defined by the three sex‐specific clusters corresponded with the default mode network (DMN). Conclusions In youth without psychiatric diagnoses, traumatic experiences are associated with an alteration of rsFC in brain regions corresponding with the somatomotor network. Associations differ in direction between males and females in brain regions corresponding with the DMN, suggesting sex‐specific responses to early exposure to trauma.